A case study of frontal variant of Alzheimer disease: Neuropsychology/Neuropsychological correlates of physiologic markers of cognitive decline/Dementia. (7th December 2020) - Jia, Ziyan; Xu, Jun; Shi, Jiong; Chen, Qidong; Zhang, Qian
Abstract: Background: With the further understanding of AD, we found that it has heterogeneous clinical presentations. It is typical of early and progressive impairment of episodic memory, but we also recognized a special type—fv‐AD, which shows obvious executive cognitive impairment. We report a male patient, aged 60 years, who was clinically diagnosed with fv‐AD. He had memory impairment in the early stage of the disease, but had executive dysfunction that did not match with memory impairment, resulting in the early loss of social function. He had a history of personality change, stubbornness, delusion and hallucination. Method: Chose an fv‐AD patient and collect his clinical manifestation, neuroimaging data and cognitive assessment. Result: In clinical manifestations, it coincides with behavioral‐variant frontotemporal dementia (bvFTD), and has difficulties in differential diagnosis. Positron emission tomography(PET) with fluorodeoxyglucose showed marked hypometabolism in frontotemporal and parietal regions. The PIB‐PET showed hypermetabolism in frontotemporal, parietal and occipital regions, which was consistent with in vivo amyloid deposition neuroimaging evidence of AD pathology. Conclusion: This report mainly discusses the similarities and differences between fv‐AD and bvFTD, which is helpful for clinical differential diagnosis, enriching the clinical manifestations of this kind of patients and improving our understanding.